POxAP Precatalysts and the Negishi Cross-Coupling Reaction - Tang, Shuang-Qi; Schmitt, Martine; Bihel, Frédéric (Synthesis, 2020)
Recently developed for the Fukuyama reaction, post-oxidative addition precatalysts (POxAPs) are also very efficient in catalyzing Negishi cross-coupling reactions between organohalides and organozinc reagents. Using very low catalyst loadings, POxAPs show similar catalytic activities to those of classical precatalysts such as XPhos Pd G4 or PEPPSI-IPr, with turnover numbers of up to 93,000. POxAPs are easily prepared, are stable to air and moisture, tolerate a wide range of functional groups in the Negishi cross-coupling reaction and contribute advantageously to the arsenal of organic chemists in terms of Pd precatalysts.
Keywords: Negishi cross-coupling; organohalides; organozinc reagents; palladium; precatalyst; POxAP